Extração, Transformação e Carga de Dados Abertos como Ferramenta de Apoio ao Voto nas Eleições de 2018 - Passos, Nélson R. S.; Rodrigues, Ariel F.; Macedo, Hendrik Teixeira; Prado, Bruno O. P.; Da Silva, Gilton José Ferreira; Matos, Leonardo Nogueira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
Democracy is a political regime based on the majority's choice. However, people can only make conscious decisions if they have access to high quality information. This paper aimed to join data from different sources and to transform them in knowledge to Brazilians voters. It applied ETL (Extract, Transform, Load) methods on open and property data to build a process that covers data gathering and transformation, dataset generation, database modeling and population, public APIs development, and a mobile app as the knowledge's visualization model. As a result, for 2018 Brazil's general elections, it processed almost two million candidacies, half a million deputies' tasks and five thousand court lawsuits. Furthermore, the products released by this research reached good performance indicators: the access logs recorded more than three million hits for the public API and twelve thousand downloads for the mobile app in the last week of the first-round's political campaign.